2011
DOI: 10.1152/ajpregu.00736.2010
|View full text |Cite
|
Sign up to set email alerts
|

GABA in the paraventricular nucleus tonically suppresses baroreflex function: alterations during pregnancy

Abstract: It is well established that GABAergic inputs to the paraventricular nucleus of the hypothalamus (PVN) tonically suppress heart rate and the activity of several sympathetic nerves. However, whether GABA similarly inhibits PVN control of baroreflex function has not been previously investigated. To test this hypothesis, it was determined whether microinjection of the GABA A antagonist, bicuculline, into the PVN enhances the baroreflex in anesthetized female virgin rats. In addition, because GABAergic inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…A major contributor to this increased SNA may be reduced tonic inhibition of PVN presympathetic neurons. In addition to the previously reported decreases in GABAergic 13, 14 and nNOS-mediated 15 SNA suppression, our data suggest that tonic PVN NPY inhibition of SNA is also lessened. First, similar to the mouse, 18 we found that PVN NPY expression is decreased in pregnant rats.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A major contributor to this increased SNA may be reduced tonic inhibition of PVN presympathetic neurons. In addition to the previously reported decreases in GABAergic 13, 14 and nNOS-mediated 15 SNA suppression, our data suggest that tonic PVN NPY inhibition of SNA is also lessened. First, similar to the mouse, 18 we found that PVN NPY expression is decreased in pregnant rats.…”
Section: Discussionsupporting
confidence: 79%
“…Second, PVN NPY-induced sympathoinhibition was preserved, but the normal sympathoexcitatory response to PVN NPY Y1R blockade was abolished in pregnant rats. The failure of NPY1× to increase SNA in pregnant rats cannot be because the elevated basal SNA has reached a maximal level, since baroreceptor unloading 12, 14 and PVN nanoinjection of the GABA A antagonist, bicuculline, 13, 14 can both increase SNA further in pregnant rats. Nevertheless, our ihc data appear to conflict with studies showing that the expression of NPY [and the co-expressed agouti-related peptide (AgRP)] in the ArcN, one major source of PVN NPY inputs, is increased or unchanged during late pregnancy, 28-30 and that PVN NPY Y1R may be elevated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from others investigating the regulatory role of GABA inputs in the PVN on baroreflex control using pharmacologic techniques (intravenous infusion of nitroprusside and phenylephrine) documented an increase in baroreflex sensitivity after GABAa inhibition with bicuculline, and this was specifically due to changes in baroreflex sensitivity during the hypotensive state induced by the intravenous infusion of nitroprusside (32). Also, intravenous nitroprusside may change nitric oxide levels, potentially affecting GABA mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, increasing MIF levels in the PVN of Sprague-Dawley rats had the seemingly adverse effect of reducing baroreflex sensitivity. The PVN exerts tonic inhibition on baroreflex function (46); however, the mechanism accounting for the effect of excess MIF to inhibit baro- GFP time control, n ϭ 6; MIF time control, n ϭ 7-8; GFP stress, n ϭ 9; MIF stress, n ϭ 13. *P Ͻ 0.05 MIF vs. GFP, #P Ͻ 0.05 stress vs. time control.…”
Section: Discussionmentioning
confidence: 99%